The Frmpd3 Protein Regulates Susceptibility to Epilepsy by Combining with GRIP and GluA2 - Yan Jia; Jinqiong Zhan; Pengcheng Huang; Xiaobing Li; Daojun Hong; Xi Lu (Current Issues in Molecular Biology)
Frmpd3 (FERM and PDZ Domain Containing 3), a scaffold protein potentially involved in excitatory synaptic function, has not been thoroughly characterized in terms of its expression and functional role in vivo. Here, we investigated the distribution of Frmpd3 in the central nervous system and its potential regulatory role in epilepsy, a neurological disorder characterized by disrupted excitatory–inhibitory balance. The distribution of Frmpd3 throughout the mouse brain was investigated by immunofluorescence. Western blotting was conducted to examine potential alterations in Frmpd3 protein expression in the hippocampus of a pentylenetetrazol (PTZ)-induced chronic epilepsy model. Using stereotaxic techniques, we delivered Frmpd3 siRNA-AAV9 into the hippocampal CA1 region to achieve targeted protein knockdown. Then, the functional consequences of Frmpd3 depletion were assessed through behavioral observations and electrophysiological recordings in PTZ-treated mice. Finally, protein–protein interactions were investigated using immunoprecipitation and Western blot analysis. Immunofluorescence analysis revealed Frmpd3 expression in cortical, hypothalamic, cerebellar, and hippocampal neurons of adult mice. Subcellular localization studies demonstrated predominant distribution of Frmpd3 in the excitatory postsynaptic density (PSD) of hippocampal CA1 neurons, with additional expression in inhibitory neurons. Quantitative analysis showed significantly elevated Frmpd3 protein levels in the hippocampus of PTZ-induced epileptic mice compared to controls. Frmpd3 knockdown in the CA1 region resulted in the following: (1) reduced seizure frequency, (2) prolonged seizure latency, and (3) decreased incidence of PTZ-induced generalized seizures. Local field potential (LFP) recordings demonstrated that seizure amplitude tended to be reduced, and epileptic discharge durations tended to be shorter in Frmpd3-depleted mice compared to controls. Furthermore, we observed decreased membrane expression of the AMPA receptor GluA2 subunit in the hippocampus of Frmpd3 knockdown mice. Molecular interaction studies revealed that Frmpd3 forms complexes with glutamate receptor-interacting protein (GRIP) and GluA2. Our findings identify Frmpd3 as a novel regulatory scaffold protein that modulates epileptic susceptibility through molecular interactions with GRIP and GluA2. The underlying mechanism appears to involve Frmpd3-mediated regulation of GluA2 trafficking from the cytoplasm to the membrane, ultimately enhancing neuronal excitability through increased membrane expression of GluA2-containing AMPA receptors.